Beyond rationality in organization and management - McMurray, Robert, 1972-; Linstead, Alison, 1971- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Spanning the 20th and 21st centuries, the writers considered in this first book of the Routledge Focus on Women Writers in Organization Studies series make an important contribution to how we think about rationality in managing, leading and working. It provides a space in which to think differently about rationality, challenging dominant masculine logics while positioning relations between people centre stage. A critical and intellectually provocative text, the book provides a nuanced and practical account of rationality in organizational contexts, making it clear that women have and continue to write groundbreaking work on the subject: women like Lillian Moller Gilbreth, who was at the forefront of developments in scientific management, and Frances Perkins, who was the first female US cabinet secretary. Both are important not only for what they achieved but also as illustrations of the ways in which women have been written out of the accounts of managing and management thought. This matters not only because credit is denied to those who deserve it, but also because it impoverishes our understanding of complex organisational phenomenon. Where so much extant writing on managing and organizing is preoccupied with abstract notions of structure, strategy, metaphor and machines, the writers considered here explain why effective working and managing is primarily about seeing and working with people. Writers such as Arlie Hochschild, Mary Parker Follett and Heather Heopfl remind us that rationality cannot be decoupled from emotion or, where a system is to be rationalised, then it should start with and enhance the lives of people - be designed with people at the centre. In this sense, the book is not arguing for a wholesale rejection of rationality. Rather, authors call on readers to move beyond a preoccupation with rationality for its own sake, seeing it instead as a useful and highly contestable aspect of organizational life. Each woman writer is introduced and analysed by an expert in their field. Further reading and accessible resources are also identified for those interested in knowing more. This book will be relevant to students, researchers and practitioners with an interest in business and management, organizational studies, critical management studies, gender studies and sociology. Like all the books in this series, it will also be of interest to anyone who wants to see, think and act differently.
OCLC-licensed vendor bibliographic record.
Keywords: Management -- Study and teaching; Organizational sociology -- Study and teaching; Women social scientists; PSYCHOLOGY / Social Psychology; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Organizational Behavior